Penilaian Autentik Pimpinan Menggunakan Analisis Varians untuk Pengambilan Keputusan: Authentic Assessment of Leadership Using Variance Analysis for Decision Making - Isak Iskandar; Eni Nur’aeni; Yayan Muzayyan; Diah Sa’adiah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
A leader holds full responsibility for all risks that occur in the institution they lead. Every policy taken is the result of a thorough evaluation process. In the context of leadership, authentic assessments conducted by leaders can be an important basis for strategic decision-making. This aims to ensure that decisions taken are not only on target but also able to achieve organizational goals effectively. The involvement of subordinates in the decision-making process is also a wise step, because it can increase a sense of ownership of the decision and make them part of the control process in carrying out tasks. This study used a quantitative method with a one-way analysis of variance (ANOVA) approach in several groups of Principals' Working Meetings (MKKS) in Banten Province. Data were obtained through the distribution of questionnaires, which resulted in the following distribution: Strongly Agree (34.13%), Agree (37.38%), Neutral (17.69%), Disagree (7.69%), and Strongly Disagree (3.13%). Based on the results of the one-way ANOVA test with a calculated F-value = 3.38 and F-table = 2.11, the results obtained are that the calculated F-value? F-table. Thus, H? is rejected, which means there is a significant influence between the authentic assessment of leaders on decision-making in the MKKS forum in Banten Province. These results indicate the importance of the presence of authentic assessment as an indicator of leadership success in the educational context.